Perbedaan motivasi berpretasi dan dukungan sosial teman sebaya antara mahasiswa perantau dan non perantau di Fakultas Kedokteran Universitas Udayana - Choirunisa, Nurul Lady; Marheni, Adijanti (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2019)
Every individual is entitled to get the highest education, one of them by taking lectures in college. The main goal of becoming a student is to achieve academic achievement. There are several factors that influence, among others, achievement motivation and peer social support. Achievement motivation as individual desire to undergo the process of lecturing well, while the social support of peers as a help from friends in various forms. Students of immigrants and non-immigrants have different conditions, so this study aims to see the difference between achievement motivation and peer social support owned by students. This study uses quantitative methods with the subject of 238 students who are studying at Faculty of Medicine Udayana University selected using cluster random sampling technique. The research instrument used achievement motivation scale and peer social support. Data analysis using Independent Sample T-Test with result of significance equal to 0,001 (p <0,05) on achievement motivation with higher immigrants empirical mean that is 110,38 and empirical mean of non- immigrants 106,98. Results of social support significance of 0.047 (p <0.05) with the higher immigrants empirical mean of 173.70 and non-immigrant empirical mean of 170.95. The results of this study indicate there are differences in achievement motivation and social support of peers between immigrants and non immigrant students at the Faculty of Medicine Udayana University. Overseas students have higher achievement motivation and social support than non migrant students. Keywords: Achievement motivation, immigrants, non-immigrants, peers social support.